Analisis kemampuan komunikasi siswa dengan metode pendekatan Realistis Mathematic Education (RME) - Annisa Nur Safitra Hasibuan; Eka Khairani Hasibuan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to describe how students' mathematical communication skills are written and how are students' mathematical communication skills orally using a realistic approach to RME (Realistis Mathematic Education) in class 7 students of MTs Nur Ibrahimy. The type of research used is qualitative research with a qualitative descriptive approach, through data collection in the form of observation, interviews and documentation and data analysis techniques used in the form of data reduction, data display, and conclusion drawing/verification. The results of the study show that the realistic approach to RME (Realistis Mathematic Education) is closely related to students' ability to communicate integer material correctly and correctly, both in writing and orally, through the steps of giving problems in everyday life, giving encouragement and developing problems. more deeply and consider ways or steps to examine and research and finally give students assignments. It is hoped that this research will contribute to school principals and teachers in improving students' ability to communicate mathematically through a realistic approach to RME (Realistis Mathematic Education) so that optimal learning outcomes are achieved effectively and efficiently